The Influence Of Public Perception On The Quality Of Health Services (A Study At Suli Community Health Center, Salahutu District, Central Maluku Regency) - Ratsuala, Remsi Dominggus; Setitit, Ignasius; Jacobs, Samie L. (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the influence of community perceptions on the quality of health services at the Suli Public Health Center. Using a quantitative approach with a sample of 73 respondents, data were collected through questionnaires and analyzed using descriptive and inferential statistics. The research instruments were proven valid and reliable, with Cronbach’s Alpha values of 0.876 and 0.902. The classical assumption tests normality, multicollinearity, and heteroscedasticity were fulfilled, validating the feasibility of linear regression analysis. The results of the simple linear regression show a positive and significant relationship between community perception and service quality, with a regression coefficient of 0.453. The t-test and F-test results also confirm the significance of this influence, with p-values less than 0.05. The coefficient of determination (R²) was 0.242, indicating that 24.2% of the variation in service quality can be explained by community perception. The findings highlight the important role of community perception in shaping the quality of health services, and suggest that future service improvements should consider public opinion as a key factor.